Water in Circular Economy and Resilience : The Cases of Tugu Tirta and Adhya Tirta Batam, Indonesia - World Bank (World Bank, Washington, DC, 2021)
There are close to four hundred water utilities in Indonesia with varied performance and capacity but only around half are considered well performing. Inefficient operations has been identified as one of the key issues hampering performance and reducing utilities’ capacity to provide reliable water supply services. If not addressed, water utilities’ inefficiency could hamper government efforts to achieve development targets. High rates of nonrevenue water (NRW) pose a major challenge to the operational efficiency of many of Indonesia’s water utilities. This case study is part of a series prepared by the World Bank’s Water Global Practice to highlight existing experiences in the water sector. The purpose of the series is to showcase one or more of the elements that can contribute toward a Water in Circular Economy and Resilience (WICER) system. This case focuses on interventions on the utility’s supply side to increase efficiency and minimize waste.